RAGAM BAHASA PADA TUTURAN PEDAGANG IKAN KABUPATEN DEMAK DITINJAU DARI KAJIAN FONOLOGI - Rifqiana Azizah; Turahmat Turahmat; Oktarina Puspita Wardani (Jurnal Pendidikan Bahasa Indonesia, 2017)
Indonesian people have so many tribes that various language are used. It happens for many cultures growing around citizens. Various language used by fishmongers also have unique varieties that could be distinguished from other sellers. It could be seen when they sell their goods. Language variety viewed from phonology aspect could interpret phoneme addition, reduction or change. Fishmongers’ speech in Demak market have their own unique characteristics. These varieties were the attractions of this research. Purpose of this research was to describe fishmongers’ speech in Demak Regency based on phonologic study. The used method was qualitative description method which do not need numbers. Data needed by this research were in forms of words, phrases, sentences and speeches of fishmongers in Demak Regency. Result of the study described language variety as viewed from phonologic study. There were phoneme change (to make buyers clearly heard what fish was being offered), phoneme reduction (to make sellers quickly delivered speech to offer their fish to buyers), and phoneme addition (to ease fishmongers to deliver speech) so that fishmongers’ aim to sell their fish could be accepted by the buyers.